Effectiveness of PGF2α Hormone Dosage Using the IM Method to Synchronize Estrus in Peanut Goats - Semuel Erubun; Jusak Labetubun; Demianus F. Souhoka (Cita konsultindo, 2024)
The purpose of this study is to assess the effectiveness of administering doses of PGF2ɑ hormone in regulating estrus synchronization in Kacang goats. The research was conducted in Sohuwe Village with variables including the time of onset of estrus, percentage of estrus, symptoms of estrus, and duration of estrus. In the study, it was found that administering doses of PGF2α hormone at 0.4 ml, 0.6 ml, and 0.8 ml to bean goats resulted in significant differences in the onset and duration of estrus. This indicates different variations in estrus response between the different doses. Estrus symptoms observed in all animals included restlessness, mounting and standing still when mounted, decreased appetite, swelling and redness of the vulva, and the discharge of transparent mucus from the vulva. The estrus percentage reached 100% in all animals. It can be concluded that the doses of PGF2α hormone used are still effective for estrus synchronization in Kacang goats. However, the results indicate that the 0.8 ml dose (P3) had a better influence on the onset and duration of estrus compared to the 0.4 ml (P1) and 0.6 ml (P2) doses. This indicates that the 0.8 ml dose had the most significant effect in regulating estrus in bean goats in the study.